Evaluación de los procesos de la mesa de servicios informáticos de “iPlanet Banda Ancha” utilizando como marco de referencia ITIL, para proponer mejoras en el proceso - Morejón Armijo, Victoria Estefanía (2016)
iPlanet Banda Ancha is a provider of telecommunications and internet service that extends its service to places where other providers do not reach in the cities of Quito, Guayaquil and Cuenca, the company does not sell local service operators because it has a “direct connection to international fiber optic Colombian Caribbean”. iPlanet Banda Ancha has a service desk, which is the only point of communications for all internal and external users where immediate support is offered, solving the requested requirements and these are canalizing to specialist staff. Additionally it is responsible for the operation and monitoring of telecommunications infrastructure, expansion of Internet infrastructure and coverage under the plan of annual growth, Internet service installation to new users. In order to evaluate existing processes in the IT service desk an audit was made using as a frame of reference ITIL v3. The first step was to evaluate the level of technological maturity which allowed for a preliminary information gathering, know the level of use of technology in each of the processes executed and thus select control objectives that are best suited to the company. With the results of the audit arises a proposed improvement plan with recommendations in order to the processes currently running on the service desk approach to the processes of the framework in which the audit was based.